Pemantauan Kandungan Total Coliform Dan Eschericia Coli Pada Air Bersih Di Desa Cikedokan - Nadya Ulfani Sara; Dodit Ardiatma; Putri Anggun Sari (DPPM Universitas Pelita Bangsa, 2022)
One source of clean water that is still widely used by the community is well water and the quality of this water must be considered. Several diseases that attack humans can be transmitted and spread through water. Therefore microbiological tests on well water must be carried out to determine the source of the quality of the water used. It is important to monitor the quality of clean water in Cikedokan Village microbiologically to find out whether there is a decrease in water quality caused by Total coliform and Escherichia coli bacteria. The sampling point was determined by purposive sampling. The number of sampling points is 15 points. The sample taken is a sample of groundwater residents of Cikedokan Village. The samples were then analyzed for later comparison with the Quality Standards of the Minister of Health Regulation Number 32 of 2017. The results of the analysis showed that there were 13 well water samples in Cikedokan Village that did not contain polluted bacteria and there were 2 well water sample points containing Total Coliform and E.coli of 1600 CFU/100 ml and 130 CFU/100 ml so it can be concluded that the two points have experienced a decrease in the quality of clean water.